Interaction between HIV/AIDS and infective endocarditis in Africa: a retrospective case report and literature review - Mvungi, Robert Sostenes (My University, 2009)
In Africa, infective endocarditis (IE) is still a disease of young adults with underlying rheumatic heart disease (RHD). As of 2006, almost two-thirds of all persons infected with human immunodeficiency virus (HIV) are living in sub-Saharan Africa. Southern Africa thus remains the epicentre of the global HIV epidemic. The HIV sero-prevalence data reported in Southern Africa are as high as 20% - 30% of the adult population aged between 15 and 49 years. In South Africa, the prevalence of HIV among adults aged 15 - 49 is 18.8%. Based on a simple extrapolation, there is a higher possibility of encountering a significant number of patients infected with HIV and underlying RHD with IE in Southern Africa than in any other part of the world. In Africa because both HIV and valvular heart disease are relatively common, the co-existence of the two conditions in individual patients is not rare. Despite the major advances in diagnosis and management of this classical disease, the overall mortality rates for both native-valve and prosthetic-valve endocarditis remain as high as 20 to 25 percent after 1 year and at 50% after 10 years. However, the mortality rate varies, depending on a number of factors, such as: • the causative microorganism • the presence of complications • the development of perivalvular extension or a myocardial abscess • neurological events • the existence of conditions such as congestive heart failure • renal failure • severe immunosuppression due to HIV infection in intravenous drug abusers • the use of combined medical therapy and surgical therapy in appropriate patients. vi The clinical outcome of infective endocarditis in HIV patients is poor, severe immunodeficiency in IVDAs with IE has been reported to be associated with poor outcome. However, such an association has never been documented in non-IVDAs, particularly in Africa, where the expected majority patients with HIV and IE are non- IVDAs. The clinical profile including bacteriology of infective endocarditis in HIV patients is different from HIV uninfected patients. The clinical impact of the HIV epidemic on infective endocarditis in Africa has not been elucidated in the world literature and there is, moreover, a paucity of literature describing this clinical entity of HIV and IE in Africa. Objective The objective of this study was to highlight the co-existence of infective endocarditis in HIV positive, non-intravenous drug abuse in South Africa and Africa by: reporting three cases admitted at the researcher’s institution within a period of two months; and undertaking a literature review. Methods This was a retrospective case report and literature review study of IE in HIV infected patients. Three HIV positive patients with IE and with or without underlying chronic rheumatic heart disease were reported. The patients were admitted at the researcher’s institution within a period of two months. All three patients did not report intravenous drug abuse. However, all patients died within a short period of admission to the hospital. The systematic review of cases published in the literature was delivered from MEDLINE SEARCH from January 1985 to December 2006. The following key words were used: Human Immunodeficiency Virus, Acquired Immunodeficiency Syndrome, Rheumatic Heart Disease, Infective Endocarditis, and Intravenous Drug Abusers and Non-Intravenous Drug Abusers. Most of the articles were identified in English; where articles were identified in Spanish and French, only abstracts were used. vii Literature emanating from Africa was emphasized. In addition, the references quoted in this study were reviewed for relevance on the topic. Results Three patients with definitive IE and infected with HIV were reported: one patient was without underlying chronic rheumatic valvular heart disease and two showed underlying chronic rheumatic valvular heart disease. There are few reported studies of IE not related to intravenous drug abuse in HIV infected patients in the literature, which is probably attributable to the reported low prevalence of IE in this sub-group of patients. Most of these published studies are limited to a series of case reports and very little data or reports originate from Africa. Conclusion The clinical pattern of IE in HIV positive patients who are not IVDAs is not well described in literature. However, in this anecdotal case report, the three patients studied retrospectively had a poor outcome. Based on this anecdotal report of three cases described, if an extrapolation was done from these numbers and a prospective analysis performed, we would observed a substantial number of non-IVDU cases with infective endocarditis and HIV/AIDS in Africa. The literature review in its current form may shed some light on HIV and IE in non-IVDU patients, but doesn’t specifically address the issue of the potential co-existence of HIV and IE in Africa. Given the high prevalence both HIV/AIDS and rheumatic valvular heart disease in Africa, in future, we are more likely to see a significant proportion of patients with IE and underlying rheumatic valvular heart disease who are coincidentally HIV infected. There is a useful need for prospective studies describing the prevalence and outcome and for subsequently defining the management of this condition in Africa.
M.Med.(Internal Medicine), Faculty of Health Sciences, University of the Witwatersrand, 2009.
Keywords: HIV/AIDS; endocarditis; Africa; case report; literature review